Education for democratic citizenship in a comparative perspective - Spajić-Vrkaš, Vedrana (2013)
The study was coordinated by the CIVITAS BiH and with a financial support of the US Democracy program and US Embassy in Bosnia-Herzegovina. in 10 countries (Albania, Bosnia and Herzegovina, Bulgaria, Croatia, Kosovo, Macedonia, Montenegro, Romania, Serbia and Slovenia) by the national research teams on a total sample of 2314 secondary school students attending the final year of the gymnasium and vocational schools. However, this report relies on the data compiled from a total sample of 1594 respondents from seven countries. Due to technical problems with the national databases, the data from three countries (Kosovo, Macedonia and Bulgaria), are not included in this report. Moreover, despite the fact that the demographic structure of the national samples was agreed upon within the research consortium in a way that it would be representative of gender, school type and regional country differences, the national teams found it difficult to comply with these standards due to financial and administrative constraints. The result is that national samples differ to a great extent in all three criteria, and especially in the gymnasium-vocational school ratio which has been shown to be highly predictive for the outcomes of human rights and citizenship learning. This means that the data should be read and interpreted contextually. Namely, the outcomes of different policies, approaches and practices in civic and human rights education are deeply nationally coloured, despite similar external influences of, e.g. the Council of Europe, European Commission, INGOs, NGOs and other countries. Notwithstanding, the data do allow us to identify the most outstanding similarities and dissimilarities in the region without rigid comparison procedures. The analysis of national reports that contain an introduction on the inclusion of civic and human rights education in their respective countries reveals the existence of various terms and concepts used to denote learning for human rights and citizenship in elementary and secondary schools. Although all national curricula and/or legal and strategic documents on education stress the importance of promoting an active and responsible citizenship and citizenry through formal education, which is in line with the recommendations of the Council of Europe, citizenship education, civic education and human rights education are more generic terms which stand for different conceptualizations as well as practices in this field. This should be linked to, inter alia, specific national histories and educational traditions, especially in reference to whether and to what extent schools are seen as instruments for the “creation” of citizens and of democratic development. An important question in this context is whether and to what extent are the principles of human rights, cultural pluralism and equality seen as the foundations of a competent citizen by both the policy-makers and relevant professional groups. This question also explains a variety of the modes of integration of civic and human rights education in the formal system of education. Apart from Croatia, in which active citizenship is still officially promoted as a part of existing school subjects (such as Politics and Economy in secondary education), a set of cross-curricular themes or a series of extra-curricular activities, in all countries in the region civic education is mandatory, although its mandatory status differs considerably. The findings of the regional pilot research on students’ civic and political knowledge, on their attitudes about learning human rights and citizenship in school, as well as on their civic and political culture indicate that the acceptance of the civic and human rights education as an umbrella-term is a poor indicator of the quality and practice of such education and training, providing that, at least at the European level, it is agreed that such education should promote a knowledgeable, active and responsible citizen, i.e., the citizen who can make informed decisions and act upon such decisions considering the rights of the others and the condition and needs of a society as a whole. Different conceptualizations of learning for citizenship in school are responsible for differences in educational focuses, structures, contents and methodologies, which necessarily produce the differences in civic and political knowledge, skills and attitudes of students that the regional pilot-study also showed. The results of our research support this thesis. Students do demonstrate, at the individual and country level, great variations in all three categories surveyed (knowledge, attitudes about learning for citizenship in school and political culture). However, in all three categories there are also remarkable similarities that shall be discussed further.